Three notes on Osip Mandelstam’s biography - Alexander Mets (Russian Academy of Sciences. A.M. Gorky Institute of World Literature, 2019)
The first note discusses biographies of the Sinani (1851–1941) and Monvizh-Montvid (1890s — 1941) family members. The second note discusses the “Social Revolutionary context” of the trip to a secret meeting in Rayvola described by Mandelstam. The third note discusses the genre relatedness of Mandelstam’s epigraph to the poem “Delirium” by V.K. Shileiko and Shileiko’s epigraph to the Sumerian-Assyrian incantation. Archival materials of Police Department Special Division and of the 1st and 2nd Socialist Revolutionary Party Congresses are involved in the consideration and argumentation.